Activation of Combustion Process of Anthracite by Metal Nitrates; Combustion Science and Technology; Vol. XX, iss. X - Larionov K. B. Kirill Borisovich; Kaltaev A. Albert; Berezikov N. I. Nikolay Igorevich; Zenkov A. V. Andrey Viktorovich; Gorshkov A. S. Alexander Sergeevich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich (2022, 2022)
Title screen